Effectiveness of Animated Video-Based Health Education on Adolescent Knowledge of HIV/AIDS at SMA Negeri 15 Semarang - Nanang Qosim; Melyana Nurul Widyawati; Kharismana Umia Wulandari (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
HIV/AIDS is an infectious disease with a high risk of transmission among adolescents, primarily due to limited knowledge and lack of accurate information. One effective strategy to address this issue is through health education, particularly using engaging media such as animated videos to enhance delivery and retention. This study aimed to determine the effect of health education using animated video media on increasing adolescent knowledge about HIV/AIDS. The research employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 40 adolescents participated and received an intervention in the form of education through animated video. Data were collected using a structured questionnaire with 30 multiple-choice items administered before and after the intervention. Based on the results, before the health education intervention using animated video media, most respondents (25 people or 62.5%) were in the good knowledge category, 12 respondents (30%) were in the sufficient category, and 3 respondents (7.5%) were in the lacking category. After the intervention, all respondents (100%) were in the good knowledge category, with no respondents in the sufficient or lacking categories. The statistical test showed Z = -4.939 and p = 0.000 (p < 0.05), indicating a significant difference. Health education using animated video media is effective in increasing adolescent knowledge about HIV/AIDS.